Strengthening Moral and Material Support for Lupus Patients and Their Families at the Kupu Parahita Indonesia Foundation Through Cinematherapy - Handono, Kusworini; Dewi, Elvira Sari; Desfryda, Elynca Putri; Dwinadella, Sephia; Putri, Choirinnisa Meilia Ayu; Kalim, Handono; Wahono, Cesarius Singgih; Barlianto, Wisnu; Erawati, Dini Rachma; Pratama, Mirza Zaka; Sari, Tita Luthfia; Nurdiana, Nurdiana; Kusuma, Zaenal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2023)
Lupus patients and their families require adequate support to manage the disease's progression. This community service aims to help the Kupu Parahita Indonesia Foundation provide strengthened moral and material support for lupus patients and their families at the Kupu Parahita Indonesia Foundation. Results: The cinematherapy planned by the PKNM and Community Service Team received much positive feedback from patients and families. The sharing session expressed that patients and their families are grateful for the opportunity to enjoy free recreation together. Enthusiasm comes with enthusiasm to meet people with fellow lupus. . In conclusion, cinematherapy can help the Kupu Parahita Indonesia Foundation provide lupus patients and their families with more substantial moral and material support.